The complete mitochondrial genome of the Megopis sinica white (Coleoptera: Cerambycidae: Prioninae) - Ranran Su; Xiaoyun Wang (Mitochondrial DNA. Part B. Resources, 2020)
The complete mitochondrial genome of the Megopis sinica White was sequenced. The 15,689 bp long genome has the standard metazoan complement of 38 genes. These genes contained 13 protein-coding genes, 22 transfer RNA genes, 2 ribosomal RNA genes and 1 control reigion. The nucleotide composition of the M. sinica White mitogenome was A: 37.8%, C: 18.6%, G: 11.7%, T: 32.0%. The A + T was 69.8%.